1993
DOI: 10.1063/1.108814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface tension on the growth mode of highly strained InGaAs on GaAs(100)

Abstract: We have investigated the molecular beam epitaxy growth of highly strained InGaAs on GaAs(100) as a function of the anion to cation flux ratio. Using reflection high energy electron diffraction the evolution of the film morphology is monitored and the surface lattice constant is measured. It is found that the cation to anion flux ratio dramatically affects the growth mode. Under arsenic-rich conditions, growth is characterized by a two-dimensional (2D) to three-dimensional (3D) morphological transformation. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Previous studies have identified that group III stabilized surfaces are stable against island formation while arsenic stabilized surfaces are not [24]. These results do not contradict previous observations, but suggest that extremely arsenic enriched heterostructure surfaces found in the MOVPE environment can be stable against islanding, in contrast to the less arsenic rich MBE surfaces that almost categorically form QD for In 0.4 Ga 0.6 As deposition on GaAs.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies have identified that group III stabilized surfaces are stable against island formation while arsenic stabilized surfaces are not [24]. These results do not contradict previous observations, but suggest that extremely arsenic enriched heterostructure surfaces found in the MOVPE environment can be stable against islanding, in contrast to the less arsenic rich MBE surfaces that almost categorically form QD for In 0.4 Ga 0.6 As deposition on GaAs.…”
Section: Discussioncontrasting
confidence: 51%
“…In that case a layer-by-layer growth mode was preserved. Such a behaviour was found for InAs/InGaAs [16,17], (In,Ga)As/GaAs [18], and In(Ga)As/ InP(0 0 1) [19]. The latter epitaxial system is particularly interesting because one can investigate the effects of both strain elastic energy and surface energy.…”
Section: Introductionmentioning
confidence: 88%
“…Up to 7 InAs ML (respectively 10 In 0.82 Ga 0.18 As ML) were grown in the layer by layer mode, when the 2D-3D transition occurred between 2 and 3 InAs ML (respectively 4 and 5 In 0.82 Ga 0. 18 while the surface roughening process occurs in both cases from the very beginning at arsenic saturated growing.…”
Section: Growth Of Tensile Strained Layers Under As-rich Conditions: mentioning
confidence: 97%
“…This is because the surface is not completely arsenic-stabilized under the small pulses of AsH 3 and the release of strain by forming the dots was partly suppressed. 15,16 Unlike in conventional dot formation by the self-organization mechanism, where dot formation is completed in less than one minute, there is enough time in this step-bystep reformation of dots to insert a molecular beam in order to put dopants into the dots or to produce a composition gradient in the dots. To create a composition gradient in the dots as our first attempt, we examined the possibility of adding gallium or indium during dot reformation, and investigated changes induced.…”
Section: Step By Step Reformation Of Dotsmentioning
confidence: 98%